A possible involvement of ion transporter in tumor necrosis factor alpha and cycloheximide-induced apoptosis of endothelial cells. - Fujita, H (1999)
We examined the tumor necrosis factor alpha (TNFalpha)-induced apoptosis of vascular endothelial cells from the standpoint of ion channels. Cultured vascular endothelial cells from bovine carotid artery were used. Apoptosis was determined by a propidium iodide assay. Treatment of the endothelial cells with TNFalpha and cycloheximide for 6 h induced nuclear fragmentation in a TNFalpha dose-dependent manner (1-10 ng/ml). Concomitant treatment of endothelial cells with TNFalpha at a dose of 10 ng/ml and cycloheximide at a dose of 10 microg/ml elicited endothelial cell apoptosis as high as 23.4+/-4.1% at 6 h after administration. However, 10 ng/ml TNFalpha alone elicited a little apoptosis at 6 h after its administration (% apoptosis=4.1+/-0.8%). Cycloheximide (10 microg/ml) did not induce apoptosis at all. Concomitant treatment of endothelial cells with 1 mmol/l of 4,4-diisothiocyanatostilbene-2,2-disulfonic acid, which is a chloride bicarbonate exchanger blocker, partially inhibited the TNFalpha and cycloheximide-induced endothelial cell apoptosis. On the other hand, endothelial cell apoptosis due to TNFalpha and cycloheximide was completely inhibited by benzyloxycarbonyl-Asp-CH2OC(O)-2,6-dichlorobenzene (50 micromol/l), an inhibitor of caspase. Moreover, pyrrolidine dithiocarbanate, an inhibitor of nuclear factor kappa B (NF-kappaB), also suppressed endothelial cell apoptosis induced by TNFalpha and cycloheximide completely. These findings suggest that the endothelial cell apoptosis induced by TNFalpha and cycloheximide is closely related to not only chloride ions, but also both NF-kappaB and caspase activation. That is to say, there is a possibility that chloride ions or bicarbonate (pH) may play an important role in signal transduction such as NF-kappaB and caspase activation in the apoptosis induced by TNFalpha and cycloheximide.